UPAYA OPTIMALISASI PEMANFAATAN POTENSI LOKAL MELALUI INTEGRASI GENDER UNTUK MENINGKATKAN EKONOMI MASYARAKAT PESISIR DI DESA TIREMAN REMBANG - Nurhidayati, Anik; Sunarto, Sunarto (JAB (Jurnal Akuntansi & Bisnis), 2018)
Research with the title of Efforts to Optimize the Utilization of Local Potential through Gender Integration to Improve the Economy of Coastal Communities in Tireman Rembang Village. The village of Tireman is located along the northern coast but this does not guarantee that the quality of resources is high, this is evident in the low education of housewives. Although the education of women in the coastal areas of Rembang district is categorized as low, it does not prevent them from actively participating in the public sphere. If fish trading activities in the market are categorized as workers outside the home, it can be said that coastal women in Rembang district are more dominant than men, including in terms of meeting household economic needs.The problem of women's roles like this is not considered as the main one. Women's economic activities are considered as a complement that only helps the work of men or husbands. Economic activities for the service of coastal women, especially non-economic institutions but have proven to be very helpful in their economic development. Development of economic institutions like this can be done to the extent that women are involved because of the subject in developing such economic organizations. The participation of the government, men and outsiders in the development of women's economic organizations should only be more 'complementary'.Â Keywords: gender, coastal communities, economic growth